2005
DOI: 10.1159/000089353
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Patients for Early Stroke Treatment with Penumbra Images

Abstract: Review of results of experimental and clinical studies indicates that the area of physiologically impaired, but potentially salvageable, tissue surrounding the central core of focal cerebral ischemia that develops shortly after onset of vessel occlusion is complex and dynamic with severity and duration thresholds for hypoxic stress and injury that are specific to tissue site, cell type, molecular pathway or gene expression investigated, and efficiency of collateral or residual flow and reperfusion. Identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This approach offers the possibility of using individual patient-specific physiologic data, rather than artificial time criteria, for decision making. 36,37 There are shortcomings in our study. The number of patients was small, but sufficient to demonstrate that CBV abnormalities can be recognized.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This approach offers the possibility of using individual patient-specific physiologic data, rather than artificial time criteria, for decision making. 36,37 There are shortcomings in our study. The number of patients was small, but sufficient to demonstrate that CBV abnormalities can be recognized.…”
Section: Discussionmentioning
confidence: 88%
“…Calculation of abnormality volumes of Group 1 revealed that the CBV volumes increased from the pretreatment CBV studies to the immediate posttreatment FPCT CBV and the follow-up MSCT stroke lesion volume (37 . Correlation between the volumes observed on the pretreatment PCT CBV studies and those on the immediate posttreatment FPCT CBV studies was poor (r ϭ 0.6, P Ͼ .05).…”
Section: Analysis Of Cbv Abnormality Volumementioning
confidence: 99%
“…This was confirmed by thrombolytic treatment which reversed critical ischaemia and decreased volume of final infarcts. In patients, the existence of penumbra is now generally accepted and indeed it can be visualized by studies of mismatch on MRI (magnetic resonance imaging) and PET (photon emission tomography) [9]. DWI (diffusion-weighted imaging) in combination with PWI (perfusion-weighted imaging) has become a widely accepted modality for the selection of patients for acute therapy, a mismatch between these procedures suggests viable 'penumbral' tissue.…”
Section: Angiogenesis After Stroke: Evidence For Its Occurrence and Imentioning
confidence: 99%
“…For example, the C-arm CT softtissue images can reliably exclude intracranial hemorrhage, the angiographic reconstructions can help evaluate proximal vessel occlusion, and the PBV maps provide patient-specific physiologic data that can potentially be used, instead of the more generalized and nonspecific time criteria, in selecting appropriate patients for acute stroke interventions, particularly when a significant delay exists between initial imaging and patient arrival in the angiography suite. 4,20 Similarly, in the patients with aneurysmal SAH who develop delayed clinical deterioration, the PBV maps can be used to determine the hemodynamic significance of vessel narrowing detected on catheter angiography and to identify any ongoing ischemia or established infarcts, thus guiding the angioplasty procedures. For these applications, extended craniocaudal coverage allowing whole-brain PBV measurements would be particularly beneficial-for example, the changes related to vasospasm may be multifocal or global in nature and the acute ischemic stroke may be in a distribution located outside the traditional supratentorial coverage of CTP and may thus be better evaluated with extended craniocaudal coverage of C-arm CT PBV.…”
Section: Figmentioning
confidence: 99%